2022
DOI: 10.1038/s41598-022-24078-9
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of wastewater in wetlands using reed plants and biochar

Abstract: To cope with water crisis, wastewater reuse has been introduced as a potential source for irrigation. On the other hand, irrigation with wastewater may negatively affect the surroundings. In this study, reed plant (Phragmits australis) and its biochar were tested as low-cost treatments to enhance the efficiency of wastewater reclamation in wetlands within only 72 h. The investigated water was of low irrigation quality and exhibited high contents of BOD5 and fecal coliform. Moreover, this water contained high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Another possibility of optimizing processes involving CWs, reducing the time needed to remove contaminants in VFCW, is the use of biochar from the plant used in the treatment unit. When using biochar obtained from Phragmits australis, a significant reduction was observed in fecal coliforms, COD and BOD, and the metals Cu, Mn, Cd, and Al in only 72 h [64]. Those results indicated that the wastewater quality was highly improved by the biochar treatment.…”
Section: Hybrid Cw Configurations and Combined Technologies Facing Em...mentioning
confidence: 88%
See 1 more Smart Citation
“…Another possibility of optimizing processes involving CWs, reducing the time needed to remove contaminants in VFCW, is the use of biochar from the plant used in the treatment unit. When using biochar obtained from Phragmits australis, a significant reduction was observed in fecal coliforms, COD and BOD, and the metals Cu, Mn, Cd, and Al in only 72 h [64]. Those results indicated that the wastewater quality was highly improved by the biochar treatment.…”
Section: Hybrid Cw Configurations and Combined Technologies Facing Em...mentioning
confidence: 88%
“…However, it was still not enough to reach reuse levels, with stricter requirements regarding the removal of the main physical, chemical, and biological parameters. Moreover, contaminant desorption mechanisms for this type of biochar must be considered in further investigations [64].…”
Section: Hybrid Cw Configurations and Combined Technologies Facing Em...mentioning
confidence: 99%
“…Recycling agricultural waste can significantly reduce greenhouse gas emissions, with over 5.6 billion mega grams of carbon potentially sequestered from the 18 billion wasted annually worldwide [80]. This can be achieved by converting organic residues into biochar, produced under limited oxygen conditions [81][82][83][84][85][86]. Biochar reduces easily oxidized carbon content, decreasing microbial metabolic activity by 47% [87], leading to longer soil retention when used as a soil amendment [88][89][90] or organic fertilizer [91,92].…”
Section: Reduced Waste and Emissionsmentioning
confidence: 99%
“…Shale deposits, rich in clay minerals (Wilson and Wilson, 2014), can be used successfully to improve the characteristics of sandy soils (Eldardiry and Abd El-Hady, 2012;Hassan et al, 2016); yet contaminant founds in these shales should be lessened, prior to their use, to meet the acceptable environmental levels (Khurramovna et al, 2021). Potentially toxic elements are of special concern because these contaminants do not undergo biodegradation (Hashim et al, 2017;Abbas and Bassouny, 2018;Farid et al, 2019); hence possessing long term negative environmental impacts (Abdelhafez et al, 2015;Elshazly et al, 2019;Abdelhafez et al, 2021;Sarhan et al, 2021;Abd-El-Hady and Abdelaty, 2022;Asaad et al, 2022;Hussein et al, 2022;El-Shwarby et al, 2022;Mekawi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%